Personalized giving: Configurational approach in examining demographics, morality, and prosocial intentions. Issue 3 (3rd July 2019) - Septianto, Felix; An, Jake; Soegianto, Bambang
ABSTRACT: Prior research in charitable giving and prosocial behavior has identified that demographic and psychological factors can influence consumer intentions to donate. However, such research has mostly examined the net effects of such factors. The current research aims to address this important issue by employing fuzzy-set qualitative comparative analysis (fsQCA) and exploring different combinations of moral emotion, moral judgment, moral identity, and demographic factors that lead to higher customer intentions to donate time and money. In doing so, this research provides concrete managerial implications by highlighting the importance of personalized and targeted marketing strategies.